THE LIFE OPTIMIZATION OF THE SEALING SURFACE OF THE ROTATING CONTROL HEAD RUBBER CORE BASED ON THE EXPERIMENT - HE YuHang; HOU ZuoFu; ZHAO JingYing; XIA ChengYu; WU JiWei; HUANG Jian; FANG Yong (Jixie qiangdu)
In the process of underbalance drilling,the rubber core of rotating control head is subject to the alternating cycle load,which is prone to fatigue failure.Firstly,the sealing principle of rotating control head is analyzed and the stress of rubber core in dynamic sealing process is obtained.Then,the Yeoh constitutive model in the deformation process was established by the tensile test of the rubber core material. Then ABAQUS software was used to establish the finite element model of the dynamic sealing of the rubber core,and the simulation of the sealing process of the rubber core during the drilling and the optimization analysis of the factors affecting the fatigue life of the sealing surface of the rubber core were carried out.In this paper,the inner diameter of rubber core is optimized,and the inner diameter size of rubber core should be matched with different outer diameter drill pipes is optimized.The paper also optimizes the lowering and lifting speed of drill pipe under different wellhead pressures.The higher the well pressure,the more likely the rubber core fatigue failure will be. The safe lowering and lifting speed of drill pipe under different pressures is obtained.At last,according to the Chinese standard,indoor seal test and field application test were carried out in the well control equipment quality supervision and inspection center of China national petroleum industry to confirm the reliability of finite element optimization,which is of great practical significance to improve the service life of rubber core and oilfield operation safety.